Resolving challenges in biomass catalytic pyrolysis by co-optimization of process and catalyst: Removal of heavy fraction in pyrolysis vapours and application of novel zeolite catalyst with high thermal conductivity. (August 2020) - Hu, Yalun; Li, Mingrui; Fang, Yunming; Tan, Tianwei
Abstract: Ex-situ catalytic pyrolysis of lignocellulosic biomass is an intriguing technology that combines thermal deconstruction of the feedstock with upgrading of the vapour and liquid intermediates. To date, in contrast with the current fossil fuel-based industrial processes, several fundamental challenges still impede its widespread deployment to generate renewable, cost-competitive biofuels and/or value-added chemicals. Catalyst improvements and process development offer a substantial opportunity to advance the technology. In this work, a novel zeolite catalyst SiC@MZSM-5 was successfully synthesized by growing ZSM-5 on SiC nanowires. The improved thermal conductivity was envisioned to minimize adverse effects of the downstream fixed-bed temperature fluctuation resulting from strong exothermic reactions during catalytic upgrading, hence fostering product distribution regulation. Concurrently, the pyrolysis process was managed to remove the heavy fractions from pyrolysis vapours by its internal recycling and forced secondary degradation, alleviating catalyst deactivation risk and thus extending the regeneration interval. The co-optimization of catalyst and process strategy improved the catalyst lifetime, optimized fixed-bed temperature distribution, and preserved the catalytic performance. Highlights: Co-optimization of pyrolysis unit operation and downstream vapours catalytic upgrading was proposed. The heavy fraction from biomass pyrolysis was removed by its internal recycling. A novel SiC@MZSM-5 was synthesized to improve catalyst bed temperature distribution. The catalyst lifetime was prolonged without the compromise of catalyst performance.